Distanzfähiges Engagement: Mit Vielfalt und Unübersichtlichkeit erwägungsorientiert-deliberativ umgehen - Blanck, Bettina (International Dialogues on Education Journal, 2016)
In a vast variety of ideas concerning life and moral issues, perspectives and concepts pluralistic democracies confront their individuals with the challenge to agree with each other as well as discuss controversial positions and thus develop their own identity. In order for such diversity to not turn out as a hazard but as a helpful medium to build up it requires an identity with the ability to get closely involved and at the same time be able to have an objective, critical, reflexive analysis of one’s own position. The article starts with an explanation of the basic ideas of the concept. Subsequently it shows how a orientation towards deliberation promotes a „deliberating in possibilities” based on dialogues and clarifying controversies with others. These dialogues start from respective individuals up to the question: „How can we properly deal with it, if we don’t know the different perspectives (yet)?” The last question points at a responsible use of „ignorance” and obscurity. An education orientated towards deliberation (Bildung) can help to build critical, reflexive competencies.